2017
DOI: 10.1016/j.jphotobiol.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Blue/violet laser inactivates methicillin-resistant Staphylococcus aureus by altering its transmembrane potential

Abstract: The resistance of methicillin-resistant Staphylococcus aureus to antibiotics presents serious clinical problems that prompted the need for finding alternative or combination therapies. One such therapy is irradiation with blue light. To determine the alterations in metabolic processes implicated in the observed antimicrobial effects of blue light, we investigated the changes in membrane potential and the presence of free-radical-producing photo-acceptor molecules. Bacterial cultures irradiated with one or two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 40 publications
3
37
0
1
Order By: Relevance
“…The emission peaks in the chromatograms indicate the presence of endogenous porphyrins. Similar studies from other investigators suggested the presence of both porphyrins and flavins in A. actinomycetemcomitans (Cieplik et al, 2014; Fyrestam et al, 2015), porphyrins, flavin adenine dinucleotide (FAD), and nicotinamide adenine dinucleotide (NADH) in MRSA (Biener et al, 2017), porphyrins in P. gingivalis ( Fyrestam et al, 2015; Yoshida et al, 2017), porphyrins in S. cerevisiae (Fyrestam et al, 2015), and porphyrins (a mixture of coproporphyrin I, coproporphyrin III, and PpIX) in Helicobacter pylori (Battisti et al, 2017a; Battisti et al, 2017b) according to the spectroscopic or chromatographic analyses. Some other studies provided the evidence that the cytotoxicity of aBL to microbes is mediated by the aBL-induced production of ROS (Cieplik et al, 2014; Galbis-Martinez et al, 2012; O’Donoghue et al, 2016; Ramakrishnan et al, 2016; Yoshida et al, 2017).…”
Section: Mechanism Of Action Of Antimicrobial Blue Lightsupporting
confidence: 74%
See 3 more Smart Citations
“…The emission peaks in the chromatograms indicate the presence of endogenous porphyrins. Similar studies from other investigators suggested the presence of both porphyrins and flavins in A. actinomycetemcomitans (Cieplik et al, 2014; Fyrestam et al, 2015), porphyrins, flavin adenine dinucleotide (FAD), and nicotinamide adenine dinucleotide (NADH) in MRSA (Biener et al, 2017), porphyrins in P. gingivalis ( Fyrestam et al, 2015; Yoshida et al, 2017), porphyrins in S. cerevisiae (Fyrestam et al, 2015), and porphyrins (a mixture of coproporphyrin I, coproporphyrin III, and PpIX) in Helicobacter pylori (Battisti et al, 2017a; Battisti et al, 2017b) according to the spectroscopic or chromatographic analyses. Some other studies provided the evidence that the cytotoxicity of aBL to microbes is mediated by the aBL-induced production of ROS (Cieplik et al, 2014; Galbis-Martinez et al, 2012; O’Donoghue et al, 2016; Ramakrishnan et al, 2016; Yoshida et al, 2017).…”
Section: Mechanism Of Action Of Antimicrobial Blue Lightsupporting
confidence: 74%
“…Increased nucleic acid release was also observed from the measurement of spectrophotometer, with up to 50 % increase in DNA concentration into the extracellular media in the case of both microbes. The above results are endorsed by the work of Biener et al, in which the authors suggested that the inactivation of bacteria by using aBL is due to the aBL-induced marked changes in the transmembrane potential, such as alterations in membrane integrity or disabling ion pumps that made the membrane more permeable to ions (Biener et al, 2017). …”
Section: Mechanism Of Action Of Antimicrobial Blue Lightmentioning
confidence: 81%
See 2 more Smart Citations
“…These phorphyrins absorb the photon energy, become excited, and jump to the triplet state. They then release the extra energy and pass it onto molecular oxygen creating ROS, which interact with numerous macromolecules within the cell causing cellular damage and leading to cell death [38].…”
Section: Mechanisms Of Pbmmentioning
confidence: 99%